José Giral, Sergio González y Eduardo Montaño. La industria química en México. México : Redacta, 1978. 343 p. - Hodara B., Joseph (Estudios Demográficos y Urbanos, 1979)
José Giral, Sergio González, y Eduardo Montano, La industria química en México, México, Redacta, 1978.